2019
DOI: 10.1111/1468-5973.12281
|View full text |Cite
|
Sign up to set email alerts
|

Variations in employees' perceptions of organizational disaster preparedness

Abstract: Few studies have sought to understand the different kinds of preparedness measures public, private and nonprofit organizations adopt and the factors motivating these organizations to adopt different kinds of preparedness measures. The present study addresses these gaps in research using perceptions from 1,960 public, private and nonprofit employees. Results indicate significant variations in public, private and nonprofit employees' perceptions of the kinds of preparedness measures their organizations adopt. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…The advantage of CM‐as‐practice is that, rather than departing from an optimum according to which firms should be fully prepared to deal with the crisis through business continuity plans, analytical methods, and specific crisis teams, it zooms in on the actors and arenas where crisis management is conducted. In line with contemporary research on crisis management (see especially, Alonso et al, 2021 ; Kim & Lim, 2020 ; Kuckertz et al, 2020 ; Tyler et al, 2020 ), our results show clearly that we should not expect these SMEs to have any of the features of the planning paradigm. Instead, they rely on established arenas and, if anything, they seem to become less reliant on input from others, which previous studies have shown to be a success factor in crisis management (Elliott et al, 2010 ; Sauser et al, 2018 ; Torres et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The advantage of CM‐as‐practice is that, rather than departing from an optimum according to which firms should be fully prepared to deal with the crisis through business continuity plans, analytical methods, and specific crisis teams, it zooms in on the actors and arenas where crisis management is conducted. In line with contemporary research on crisis management (see especially, Alonso et al, 2021 ; Kim & Lim, 2020 ; Kuckertz et al, 2020 ; Tyler et al, 2020 ), our results show clearly that we should not expect these SMEs to have any of the features of the planning paradigm. Instead, they rely on established arenas and, if anything, they seem to become less reliant on input from others, which previous studies have shown to be a success factor in crisis management (Elliott et al, 2010 ; Sauser et al, 2018 ; Torres et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…The crisis management literature has paid specific attention to the planning for potential crisis (Doern, 2016 ; Herbane, 2013 ; Runyan, 2006 ; Tyler et al, 2020 ). Common to several studies is the view that preparation for crises pays off (Corey & Deitch, 2011 ; Mitroff & Alpaslan, 2003 ; Pearson & Clair, 1998 ; Runyan, 2006 ), and that planning is key to success both for individuals and for companies.…”
Section: Crisis Management As Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of U.S. businesses and other employers have repeatedly shown insufficient levels of preparedness for even “normal” emergencies, let alone increasingly extreme disasters fueled by climate change. 35 -38 One such example comes from Hurricane Harvey, in 2017. Multiple studies indicate that climate change intensified Harvey’s rainfall, contributing to catastrophic flooding across 70% of Harris County, Texas.…”
Section: What Should Employers Do?mentioning
confidence: 99%
“…Surveys of U.S. businesses and other employers have repeatedly shown insufficient levels of preparedness for even ''normal'' emergencies, let alone increasingly extreme disasters fueled by climate change. [35][36][37][38] One such example comes from Hurricane Harvey, in 2017. Multiple studies indicate that climate change intensified Harvey's rainfall, contributing to catastrophic flooding across 70% of Harris County, Texas.…”
Section: What Should Employers Do?mentioning
confidence: 99%